STUDI KERAGAMAN SPERMATOPHYTA DI SEKITAR DANAU ASAM SUOH KABUPATEN LAMPUNG BARAT SEBAGAI BAHAN UNTUK MEMBUAT ENSIKLOPEDIA - Agus Setiawan; Achyani Achyani; Rasuane Noor (EDUBIOLOCK, 2023)
Spermatophyta diversity in Indonesia includes a high category of rank to two in the word. Higher plants are plants that have distinguished roots, stems and leaves, and have flowers as a means of reproduction. The objectives of this research were 1) to determine the species of Spermatophyta diversity around Lake Asam Suoh, West Lampung Regency, 2) to determine the status of the biodiversity around Asam Lake Suoh, West Lampung Regency, 3) to determine the diversity index and dominance index) to find out the research results of the Spermatophyta plants in Asam Lake Suoh, West Lampung Regency, it can be used as material for the encyclopedia. This research uses purposive sampling at each station. By using these 4 stations, it is hoped that it can describe a state of Asam Lake Suoh regarding the diversity of Spermatophyta. The research data showed that there were 21 species of plants included in tall plants or Spermatophyta. The results of the calculation of the Spermatophyta Diversity Index around the Asam Lake Suoh, West Lampung is H1 1, indicating that the diversity of species in a transect site is small or low. The results of the calculation of the Dominance Index of Spermatophyta around the Asam Lake Suoh, West Lampung is 0.00 <C 0.50, indicating that the Dominance Index is low. Material validation officials get the 86% score and experts get the 84%, which means that an enciclopedia into category is highly worth using.